Collaborative work as an alternative for writing research articles (2014)
Academic writing in English in our context is a significant aspect that can be innovative when a convergence model of writing stages is used along with collaborative work. This article reports on a study aimed at analyzing how collaborative work relates to undergraduate electronics students’ academic writing development in English as a foreign language at a Colombian university, following some specific writing stages. Field notes, students’ artifacts, and semi-structured interviews were the instruments used to gather information. The results showed that writing is achievable if students can follow stages and receive feedback from the teacher. Additionally, collaborative work allowed students to write research articles in an easy and dynamic way.Los escritos académicos en inglés, en nuestro contexto, representan un aspecto significativo que puede ser innovador cuando se usa un modelo de convergencia en las etapas de la escritura a través del trabajo colaborativo. En este artículo se presenta un estudio que buscó analizar cómo el trabajo colaborativo se relaciona con los escritos académicos que desarrollan en inglés los estudiantes de pregrado de ingeniería electrónica de una universidad colombiana, que seguían etapas específicas de escritura. Para la recolección de la información se tuvieron en cuenta apuntes, escritos hechos por los estudiantes y entrevistas semi-estructuradas. Los resultados muestran que la escritura es viable si los estudiantes siguen las etapas y reciben retroalimentación por parte del profesor. Así mismo, el trabajo colaborativo permitió la escritura de artículos de investigación de una forma fácil y dinámica.